Cosmopolitan war - Fabre, Cécile (Oxford Univ. Press, 2012)
Cécile Fabre defends an ethical account of war which focuses on the individual, as a rational and moral agent, over collective groups of people. She offers a new account of just and unjust war, exploring wars of national defence, civil wars humanitarian intervention, wars involving private military forces, and asymmetrical wars.